2014
DOI: 10.1371/journal.pone.0097816
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach - The Propensity to Propagate (PTP) Method for Controlling for Host Factors in Studying the Transmission of Mycobacterium Tuberculosis

Abstract: RationaleUnderstanding the genetic variations among Mycobacterium tuberculosis (MTB) strains with differential ability to transmit would be a major step forward in preventing transmission.ObjectivesTo describe a method to extend conventional proxy measures of transmissibility by adjusting for patient-related factors, thus strengthening the causal association found with bacterial factors.MethodsClinical, demographic and molecular fingerprinting data were obtained during routine surveillance of verified MTB case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…In The Netherlands, for example, one study showed that the number of positive contacts around a case increases with growing cluster size (7). In a subsequent study in the same setting, cluster size growth was not different between phylogenetic lineages after controlling for host risk factors (8). However, this study could not distinguish between transmission rates and progression to disease.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…In The Netherlands, for example, one study showed that the number of positive contacts around a case increases with growing cluster size (7). In a subsequent study in the same setting, cluster size growth was not different between phylogenetic lineages after controlling for host risk factors (8). However, this study could not distinguish between transmission rates and progression to disease.…”
mentioning
confidence: 72%
“…The phylogenetic lineages of isolates were determined using a combination of spoligotyping, the MIRU (mycobacterial interspersed repetitive unit) best match analysis offered by the MIRU-VNTRplus online tool, and RFLP similarity, as described in a previous study using the same data set (8,14). Three species (M. africanum, Mycobacterium bovis, and M. tuberculosis) and four major phylogenetic lineages of M. tuberculosis were identified: the Euro-American, Central Asian strain (CAS), East African Indian (EAI), and Beijing genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…This allows assessment of the evidence for the impact of each variant. To simplify this process, variants for which strong experimental evidence is available (e.g., from allelic-exchange experiments [30]) are highlighted in bold as high-confidence SNPs (e.g., katG315, rpoB445, rpoB450). The nomenclature used in the plain-language report is based on the M. tuberculosis H37Rv reference genome.…”
Section: Resultsmentioning
confidence: 99%
“…We quantified the host predilection to transmit TB with the PTP measure and found the cluster to have a higher score than the median PTP measure reported by a study in Netherlands. 35 Our study had five patients with a particularly high PTP above the highest reported value of 3·9, 35 potentially contributing to transmission in the population we studied. A few prior studies have characterized bacterial genetic factors that contributed to increased transmissibility.…”
Section: Discussionmentioning
confidence: 87%
“…We measured host infectiousness in the cluster using the ‘propensity to propagate’ 35 (PTP) method and identified five patients as having the highest possible score (PTP> 4). This was related to patients being younger (20-29y) males with smear positive PTB and a history of substance use (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 99%